Efficacy and safety of combined Kahook Dual Blade goniotomy with phacoemulsification in Chinese patients with primary open angle glaucoma - Lin Fu; Jiang-Tao Lou; Yue Guo; Pei-Juan Wang; Rong-Rong Le; Shu-Xia Xu; Guo-Xing Li; Yuan-Bo Liang (International Journal of Ophthalmology)
AIM: To report the one-year surgical outcome Kahook Dual Blade goniotomy combined with phacoemulsification (KDB-Phaco) in Chinese patients with primary open angle glaucoma (POAG). METHODS: This is a retrospective study included 43 eyes of 28 Chinese POAG patients with cataract who accepted KDB-Phaco and followed-up for 12mo. Intraocular pressure (IOP), glaucoma medications and surgical complications were recorded. Success 1 and success 2 was defined as 5-21 mm Hg and 5-18 mm Hg, and success plus was determined if additional criteria of IOP reduction ≥20% from baseline was reached. A corrected IOP by adding 3 mm Hg for each medication was used to do correlation test. Cox's proportional hazards regression model was used to test the hazard ratio for factors associated with surgical success. RESULTS: After a 12-month follow up, the IOP decreased from 28.1±6.3 to 13.8±3.0 mm Hg (47.92% reduction, P<0.001), and the medications used decreased from 2.0 (1.0) to 0.0 (0.0) (95% reduction, P<0.001). The mean IOP of all postoperative visits were lower than preoperative IOP (all P<0.001), so as the number of glaucoma medications (all P<0.001). Complete success 1 and qualified success 1 were 87.80% and 100.00% respectively. The complete success 1 plus and qualified success 1 plus were 85.37% and 97.56%, respectively. Totally 82.93% and 90.24% of patients got complete success 2 and qualified success 2 while 80.49% and 87.80% of patients satisfied complete success 2 plus and qualified success 2 plus. Age (r=-0.511, P=0.001) and visual acuity (VA; r=-0.321, P=0.041) were negatively correlated with postoperative corrected IOP at 12mo, while anterior chamber depth (r=0.432, P=0.005), mean deviation (r=0.617, P<0.001) and visual field index (r=0.524, P<0.001) were positively correlated with it. Preoperative VA (OR=33.092, P=0.004) and MD (OR=1.481, P=0.018) were hazard factors associated with failure based on qualified success as 18 mm Hg. The main complications of KDB were hyphema (9.30%), IOP spike (11.63%) and peripheral anterior synechia (6.98%). CONCLUSION: KDB goniotomy is a safe and effective in the treatment for Chinese POAG patients. Preoperative VA and mean deviation may predict the surgical success.